Long-Term Effect of Non-Selective Beta-Blockers in Patients With Rheumatoid Arthritis After Myocardial Infarction-A Nationwide Cohort Study - Sheng-Fu Liu; Sheng-Fu Liu; Sheng-Fu Liu; Chih-Kuo Lee; Chih-Kuo Lee; Chih-Kuo Lee; Kuan-Chih Huang; Kuan-Chih Huang; Lian-Yu Lin; Lian-Yu Lin; Mu-Yang Hsieh; Mu-Yang Hsieh; et al. (Frontiers Media S.A., 2021)
Objectives: Rheumatoid arthritis (RA) is an independent nontraditional risk factor for incidence of myocardial infarction (MI) and post-MI outcome is impaired in the RA population. Use of beta-blockers improves the long-term survival after MI in the general population while the protective effect of beta-blockers in RA patients is not clear. We investigate the impact of beta-blockers on the long-term outcome of MI among RA patients.Methods: We identified RA subjects from the registries for catastrophic illness and myocardial infarction from 2003 to 2013. The enrolled subjects were divided into three groups according to the prescription of beta-blockers (non-user, non-selective, and β1-selective beta-blockers). The primary endpoint was all-cause mortality. We adjusted clinical variables and utilized propensity scores to balance confounding bias. Cox proportional hazards regression models were used to estimate the incidence of mortality in different groups.Results: A total of 1,292 RA patients with myocardial infarction were enrolled, where 424 (32.8%), 281 (21.7%), and 587 (45.5%) subjects used non-user, non-selective, and β1-selective beta-blockers, respectively. Use of beta-blockers was associated with lower risk of all-cause mortality after adjustment with comorbidities, medications (adjusted hazard ratio [HR] 0.871; 95% confidence interval [CI] 0.727-0.978), and propensity score (HR 0.882; 95% CI 0.724-0.982). Compared with β1-selective beta-blockers, treatment with non-selective beta-blockers (HR 0.856; 95% CI 0.702-0.984) was significantly related to lower risk of mortality. The protective effect of non-selective beta-blockers remained in different subgroups including sex and different anti-inflammatory drugs.Conclusion: Use of beta-blockers improved prognosis in post-MI patients with RA. Treatment with non-selective beta-blockers was significantly associated with reduced risk of mortality in RA patients after MI rather than β1-selective beta-blockers.